ANALYSES OF CONNECTIVITY OF PHYSICS AND MATHEMATICS IN SECONDARY SCHOOLS (Scientific journal of the Fergana State University, 2023)
We use mathematical concepts in studying the physics subject and analyzing the physical laws in secondary schools. From a historical point of view, we can see that mathematics has played a major role in development of physics.In this article we have analyzed the connectivity of physics and mathematics in secondary schools.